What are the differences between first and second divisions of Spanish football teams? - Castellano, J.; Casamichana, D. (International Journal of Performance Analysis in Sport, 2015)
We compared the performance of teams in the first and second divisions of the Spanish soccer league (BBVA and Adelante Leagues, respectively) in 2013-14. We analysed 320 first-division (L1) matches and 335 second-division (L2) matches. Variables related to use of space (width/depth of play and height of defense) and physical performance (total kilometers)) were coded using TRACAB®, while technical-tactical actions (shots, centre kicks, corner kicks, total passes, and percentage of successful passes) were coded by OPTA®. The 42 teams were divided into four groups: top 10 and bottom 10 teams in L1 (L11 and L12) and top 10 and bottom 12 teams in L2 (L21 and L22). Significant differences were found for all the indicators, with L11 teams performing better than the other three groups for almost all variables. It is noteworthy that L12 teams performed significantly better than L21 teams in terms of width and depth of play and height of defense. Our findings add to the body of knowledge of game models employed by elite soccer teams in match situations and may help coaches to design training drills focusing on specific skills and tactics, physical requirements, and use of space to optimise game dynamics and overall performance.